2016
DOI: 10.3349/ymj.2016.57.5.1282
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Rich Fibrin Lysate Can Ameliorate Dysfunction of Chronically UVA-Irradiated Human Dermal Fibroblasts

Abstract: To determine whether platelet-rich fibrin lysate (PRF-L) could restore the function of chronically ultraviolet-A (UVA)-irradiated human dermal fibroblasts (HDFs), we isolated and sub-cultured HDFs from six different human foreskins. HDFs were divided into two groups: those that received chronic UVA irradiation (total dosages of 10 J cm-2) and those that were not irradiated. We compared the proliferation rates, collagen deposition, and migration rates between the groups and between chronically UVA-irradiated HD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 26 publications
0
21
0
1
Order By: Relevance
“…Proliferation PRF increased proliferation of mesenchymal cells, for example from bone of different origin [19, 24-26, 28, 45, 50, 66, ], bone marrow [32,39], periosteum [27], adipose tissue [37,47,68], and skin [65,48]. Also, fibroblasts from gingiva [38,44], periodontal ligament [18,52,59], papilla [30], and dental pulp responded to PRF with increased proliferation [29,31,43,54].…”
Section: Selection Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Proliferation PRF increased proliferation of mesenchymal cells, for example from bone of different origin [19, 24-26, 28, 45, 50, 66, ], bone marrow [32,39], periosteum [27], adipose tissue [37,47,68], and skin [65,48]. Also, fibroblasts from gingiva [38,44], periodontal ligament [18,52,59], papilla [30], and dental pulp responded to PRF with increased proliferation [29,31,43,54].…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…There are various methods to identify the impact of PRF on cell migration including the scratch assay [70] and the traditional Boyden chamber approach [71]. Regardless of the method used, PRF increased the migration of neural stem cells [54] along with cells of the mesenchymal lineage isolated from bone [45,64], bone marrow [72], gingiva [38,64,36], apical papilla [30], and skin [65,48]. Similarly, endothelial cells responded to PRF with an increased migration [63,72,41].…”
Section: Migrationmentioning
confidence: 99%
“…Although the challenged fibroblasts proliferation rates are less than the unchallenged fibroblasts, survival and proliferation are nonetheless partially restored. The authors proposed that the fibroblasts restoration was due to the MMP-1 tissue inhibitors released from the PRP and TGF-1 signalling ameliorated suppressed proliferation [54].…”
Section: Uva Challenged Fibroblastsmentioning
confidence: 99%
“…It is said to be a good source of several growth factors. In a study, it is found that PRF-L can significantly improve the proliferation index, collagen deposition and migration rates in chronically UVA-irradiated human dermal fibroblasts [13]. This is a new technique that requires further studies.…”
Section: Prepared Platelet-rich Lysate (Prf-l)mentioning
confidence: 99%